Ceremonies of bravery : Oscar Wilde, Carlos Blacker, and the Dreyfus Affair - Maguire, J. Robert (Oxford : Oxford University Press, 2013)
'Ceremonies of Bravery' is a study of the friendship between the prolific writer Oscar Wilde and Carlos Blacker. The two men met in the 1880s, the period when Wilde was judged by many to be at his best, and Blacker went on to become a trustee of Wilde's marriage settlement.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Dec. 20, 2012).
Keywords: Wilde, Oscar, -- 1854-1900 -- Friends and associates; Blacker, Carlos -- Friends and associates; Dreyfus, Alfred, -- 1859-1935.; Authors, Irish -- 19th century; Trials (Treason) -- France -- History -- 19th century